A guideline on guidelines: neuro-oncology guideline standards for low- and middle-income countries - Mohammad Hamza Bajwa; Mashal Murad Shah; Fatima Mustansir; Fatima Gauhar; Erum Baig; Syed Nabeel Zafar; Kaynat Siddiqui; Hafiza Fatima Aziz; Syed Ather Enam (Journal of the Pakistan Medical Association, 2024)
Guidelines for low- and middle-income countries (LMICs) are needed in complex, multidisciplinary areas such as oncology, requiring mobilising considerable resources and specialists for coordinated care. Neuro-oncology guidelines have been primarily established in countries where technological advancements and robust care pathways facilitate broad resource utilisation. In contrast, LMICs require complex and region-specific interventions to provide equitable care. The present opinion paper is a culmination of our own centre’s experience collaborating and developing loco-regional guidelines for brain tumour care, keeping in mind LMIC experiences and expertise available. We intend for the process and methodology to apply to a broader audience of other LMIC authors and clinicians collaborating with LMIC institutions to develop guidelines and clinical recommendations. Keywords: neuro-oncology, surgery, Critical Pathways, Brain Neoplasms